The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1439-0507.2010.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in virulence between fluconazole‐susceptible and fluconazole‐resistant Candida albicans in a mouse model

Abstract: Two Candida albicans isolates were collected from a HIV-positive patient with recurrent oropharyngeal candidosis (OPC). One isolate was taken during the first episode of oral candidosis [fluconazole susceptible (FLU-S), minimal inhibitory concentration (MIC) = 0.25 mg l(-1) ] and the second after the patient developed refractory OPC and resistance to fluconazole (FLU-R, MIC = 64 mg l(-1)). Both isolates were clonally identical. Different in vitro studies were carried out to assess putative virulence factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…This is in contrast to the present study, where only neutral genetic markers were used for strain constructions. Another study concluded that a clinical isolate with high MDR1 mRNA levels exhibited decreased virulence (67). The finding of this study corroborated that of a separate one obtained with two fluconazole-resistant clinical isolates of C. albicans with MDR1 overexpression which exhibited low virulence in a murine model of systemic infection (25).…”
Section: Discussionsupporting
confidence: 84%
“…This is in contrast to the present study, where only neutral genetic markers were used for strain constructions. Another study concluded that a clinical isolate with high MDR1 mRNA levels exhibited decreased virulence (67). The finding of this study corroborated that of a separate one obtained with two fluconazole-resistant clinical isolates of C. albicans with MDR1 overexpression which exhibited low virulence in a murine model of systemic infection (25).…”
Section: Discussionsupporting
confidence: 84%
“…Fluconazole-resistant C. albicans is responsible for most prevalent nosocomial fungal infections and has resulted in many clinical treatment failures in immunocompromised patients, leading to the search for novel antifungal agents urgent (Schulz et al 2011;Abdelmegeed and Shaaban 2013). KAE was considered a promising candidate to enhance the efficacy of traditional antifungal drug (such as FLC).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we demonstrated that rifampicin upregulated C. albicans MDR1 expression 24 . Co-induction of CSH1 and MDR1 has also been shown for a fluconazole-resistant C. albicans patient isolate 38 . Moreover, Mdr1 has been shown to be upregulated immediately after adhesion 39 , and both CSH1 (orf19.4477) and MDR1 (orf19.5604) transcription is mediated by the multidrug resistance regulator Mrr1p 40 .…”
Section: Discussionmentioning
confidence: 69%